Yield Increase and Emission Reduction Effects of Alfalfa in the Yellow River Irrigation District of Gansu Province: The Coupling Mechanism of Biodegradable Mulch and Controlled-Release Nitrogen Fertilizer - Wenjing Chang; Haiyan Li; Yaya Duan; Yi Ling; Jiandong Lu; Minhua Yin; Yanlin Ma; Yanxia Kang; Yayu Wang; Guangping Qi; Jianjun Wang (Plants)
Agricultural production in Northwest China is widely constrained by residual plastic film pollution, excessive greenhouse gas emissions, and low productivity. Integrating biodegradable film with controlled-release nitrogen fertilizer offers a promising approach to optimize crop management, enhance yield, and improve environmental outcomes. In this study, three planting patterns (conventional flat planting, FP; ridge mulching with biodegradable film, BM; and ridge mulching with conventional plastic film, PM), two nitrogen fertilizer types (urea, U, and controlled-release nitrogen fertilizer, C), and four nitrogen application rates (0, 80, 160, and 240 kg·hm−2) were applied to systematically investigate their effects on alfalfa yield and N2O emissions from grasslands. The results showed that BM and PM increased alfalfa yield by 23.49% and 18.65%, respectively, compared to FP, while C increased yield by 8.46% compared to urea. The highest yield (24.84 t·hm−2) was recorded under the BMC2 treatment, which was 97.11% higher than that of FPN0. N2O emission flux and cumulative emissions increased with nitrogen application rate. Compared with U, C reduced cumulative N2O emissions and greenhouse gas emission intensity (GHGI) by 23.89% and 25.84%, respectively. Compared to PM, BM reduced cumulative N2O emissions and GHGI by 11.58% and 20.15%, respectively. Principal component analysis indicated that the combination of ridge mulching with biodegradable film and 160 kg·hm−2 of C was optimal for simultaneously increasing alfalfa yield and reducing N2O emissions, making it a suitable planting–fertilization strategy for the Yellow River irrigation district in Gansu and similar ecological regions.